Temporal and spatial change of habitat quality and its driving forces: The case of Tacheng region, China - Ge, Yisong; Li, Chengzhi; Zhang, Tai; Wang, Bin (Frontiers in Environmental Science, 2023)
Habitat quality assessment is an important basis for ecological restoration practice. Taking the Tacheng region as an example, the InVEST model was used to evaluate the habitat quality of the Tacheng region in five periods from 2000 to 2020, and analyze the reasons for its changes, to provide theoretical guidance for ecological restoration practice in arid areas. The conclusions were that from 2000 to 2020, the habitat quality in the Tacheng region improved slightly, and the value of the habitat index in the Tacheng region was the highest in 2010, which was 0.577, and then decreased slightly. The habitat quality in the Tacheng region was significantly influenced by land use type conversion and precipitation. The change in land use type directly affected the change in habitat quality. The study region is located in an arid area; the forest land and grassland native to the region have more vegetation communities and genera of species and can be self-sustaining and resilient to disturbance, having high scores for habitat quality. The species of arable land is a monoculture; it cannot be self-sustaining and resilient to disturbance, and though it has high vegetation cover, the value of habitat quality is lower than that of forestland and grassland. The vegetation of unused land is rare, and the ecosystem of unused land is sensitive and vulnerable; the habitat quality scores are very low. The conversion of forest land, grassland, arable land, and unused land would directly affect the value of habitat quality, and conversion was the main factor affecting the change in habitat quality. In addition, precipitation was also an important factor affecting the change in habitat quality in the Tacheng region, which affected the biomass of natural vegetation and then affected the habitat quality. The results provided the temporal and spatial change of habitat quality and its driving forces in the Tacheng region, which helps determine appropriate measures and sites in ecological restoration projects.